Disordered eating among Australian adolescents: Prevalence, functioning, and help received. Issue 3 (7th February 2019) - Sparti, Claudia; Santomauro, Damian; Cruwys, Tegan; Burgess, Philip; Harris, Meredith
Abstract: Objective: To estimate the prevalence of disordered eating (DE) among Australian adolescents and examine associations with clinical mental health problems, problems with functioning, and help received. Method: We analyzed data from the Young Minds Matter survey ( n = 2, 298, 13–17 years). We derived an index of DE severity with four levels: (1) no DE; (2) subclinical DE; (3) suspected eating disorder; and (4) lifetime eating disorder diagnosis. Results: In 2013–2014, 31.6% (95%CI 35.5–39.9) of Australian adolescents experienced DE, comprising 25.7% (95%CI 23.9–37.6) with subclinical DE, 11.0% (95%CI 9.7–12.6) with a suspected eating disorder, and 0.9% (95%CI 0.6–1.3) with a lifetime eating disorder diagnosis. DE was more common among girls (41.4%, 95%CI 37.9–44.4) than boys (34.0%, 95%CI 31.1–37.0; p = .002). Adolescents with DE, compared to those without, were more likely to experience clinical mental health problems and problems with functioning. Most adolescents with DE reported help‐seeking in the past year, commonly self‐help; around 40% used school‐based, primary care or specialist services (i.e., formal services). In multivariate analyses, the use of more specialized and intensive services was associated with more severe DE, greater problems with functioning, female gender, and 12‐month mental disorder or subthreshold mental disorder symptoms. Discussion: The implementation of mental health promotion and prevention efforts for DE, and screening for DE in school and primary care settings, may facilitate detection and appropriate help‐seeking among adolescents with DE.